A General Method to Parameter Optimization for Highly Efficient Wireless Power Transfer - Kazuya Yamaguchi; Takuya Hirata; Ichijo Hodaka (International Journal of Electrical and Computer Engineering (IJECE), 2016)
This paper proposes a new and general method to optimize a working frequency and a load resistance in order to realize highly efficient wireless power transfer. It should be noticed that neither resonant frequency nor matched impedance maximizes efficiency of wireless power transfer circuit, in general. This paper establishes a mathematical model of a commonly used wireless power transfer circuit, and derives a mathematical expression of circuit efficiency which involves a working frequency, a load resistance and the other parameters as symbols. This enables us to find the optimal workingfrequency and load resistance. The result of this paper is compared with results by a method based on resonance and impedance matching, and then clarified by a numerical example.